(untitled) (Research, Society and Development, 2020)
Agriculture has proved to be one of the main sources of greenhouse gases (GHG). Large part of this GHG is related to the production system or inadequate management. This study analyzed the effects of the High Biodiversity Silvopastoral System (SPSnuclei) on pasture cover, and carbon and nitrogen stocks when implanted on treeless pastures (PSA). The variables were measured in three situations, two areas within the SPSnuclei - area close to the nuclei (APN) and a sunny area between the (p <0.05). AEN had higher values of pasture cover and carbon stock than PSA. The SPSnuclei maintained the same pasture cover and carbon stock than PSA, even with only 90% of the total pasture area, since 10% of the pasture area was fenced off in the tree nuclei. SPSnuclei has the potential to mitigate GHG emissions from conventional livestock minimizing its impact on climate change.